Determinan keputusan menabung kaum buruh pada perbankan syariah di Kudus: Peran mediasi niat menabung - Annisa', Holif; Anwar, Saiful (Nur Science Institute, 2021)
This study aims to analyze Islamic branding, knowledge, and service quality on the saving decisions of workers, with a saving intention as an intervening variable. This type of research is a quantitative study with a population of Bank Syariah Indonesia KCP Kudus customers who make a living as laborers. The sampling technique in this study used purposive sampling, totaling 100 respondents. Workers are chosen to be unique because of their livelihood and ownership of Islamic bank accounts. The analytical tool used is path analysis. The results showed that Islamic branding, service quality, and saving intention positively affected saving decisions. Knowledge is not significant in saving decisions. Saving intention cannot mediate the influence of Islamic branding on saving decisions. Saving intention can mediate the effect of knowledge and service quality on saving decisions. The research contributes to the marketing model and services for workers. However, workers have a different segmentation from other consumers.